Predicting current and future distribution of Hovenia dulcis Thunb. (Rhamnaceae) worldwide - Bergamin, Rodrigo Scarton (2022)
Biological invasions are increasingly recognized as one of the major threats to biodiversity. The Japanese raisin tree (Hovenia dulcis) is native to East Asia, however, in southeastern South America this species has become one of the most pervasive invaders. Hovenia dulcis has many biological characteristics that favor the process of invasion and few studies have indicated changes in the structure and composition of native plant communities where this species has become invader. Given the invasiveness shown in southeastern South America, our main goal was to identify the potentially suitable habitats for this invasive species at a global scale. In this sense, we modeled the potential distribution of H. dulcis along the terrestrial areas worldwide using an ensemble forecasting approach. Additionally, the percentage of overlapping biodiversity hotspot areas with the currently suitable areas for this species was calculated. Our results revealed that the current potential H. dulcis range is equivalent to 7.88% (12,719,365 km2 ) of the terrestrial area worldwide. For the future scenarios of climate change, the potential distribution area tends to have a small reduction. However, significant suitable areas were identifed for H. dulcis range in the northern limits of the boreal distribution. Currently, around 17% of biodiversity hotspot areas overlap with the suitable areas for H. dulcis occurrence. In summary, given that the prevention is well-recognized as a more efective management action against invasive alien species, it is essential to implement policies to prevent H. dulcis introduction in suitable areas worldwide, as well as local population control, especially in biodiversity hotspots.